2018
DOI: 10.1029/2018wr022525
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Forecasting of Nitrogen Dynamics in Hyporheic Zone

Abstract: Nitrification‐denitrification processes in the hyporheic zone control the dynamics of dissolved inorganic nitrogen (DIN) species and can lead to production of nitrous oxide, which contributes to the greenhouse effect. We consider DIN dynamics in an advection‐dominated regime, wherein transport and reactions occur along streamlines crossing hyporheic sediments. Our focus is on the impact of uncertainty in both stream water quality and rate constants of the subsurface reactions on predictions of DIN concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…and the moment equations satisfied by hðxÞ and σ 2 h ðxÞ, as in Boso and Tartakovsky (2016), Boso et al (2018), and Yang et al (2019). These expressions assume the random variable h(x) and the corresponding CDF F h (U; x) to be defined on the interval ½H min ; H max .…”
Section: Appendix A: Cdf Equation For Flow In Composite Porous Mediamentioning
confidence: 99%
“…and the moment equations satisfied by hðxÞ and σ 2 h ðxÞ, as in Boso and Tartakovsky (2016), Boso et al (2018), and Yang et al (2019). These expressions assume the random variable h(x) and the corresponding CDF F h (U; x) to be defined on the interval ½H min ; H max .…”
Section: Appendix A: Cdf Equation For Flow In Composite Porous Mediamentioning
confidence: 99%
“…Empirical or phenomenological selection of the closure variables (Haworth, 2010;Pope, 2001;Raman et al, 2005) does not automatically guarantee an accurate reproduction of the first and second statistical moment of the distribution, that is, meanh(x) and variance 2 h (x). Following Boso and Tartakovsky (2016) and Boso et al (2018), we construct the closure variables and in a way that ensures that the CDF equation 7gives rise to the moment equations satisfied byh and 2 h . We start by recalling that if a random variable h is defined on an interval [H min , H max ], then the mean and variance of the CDF F h (H) arē…”
Section: Cdf Equation For Hydraulic Headmentioning
confidence: 99%
“…The self-consistent closure of Boso & Tartakovsky (2016) ameliorates this deficiency by preserving both the mean and variance. It has been used to quantify uncertainty in advection-dispersion (Boso & Tartakovsky, 2016) and advection-dispersion-reaction (Boso et al, 2018) problems.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that hyporheic exchange flux, solute transport, and consumption increase during individual flow events. Boso et al (2018) adopted a probabilistic approach to quantify the impact of uncertainty in both the temporally-variable river water and the rate constants on predictions of N 2 O emissions at the bedform scale. On the other hand, Zheng and Cardenas (2018) focused on the effects of temperature on nitrogen cycling and nitrate removal-production efficiency in bedform-induced hyporheic zones under steady flow conditions.…”
Section: Introductionmentioning
confidence: 99%